2018
DOI: 10.1002/pd.5377
|View full text |Cite
|
Sign up to set email alerts
|

Reliable detection of subchromosomal deletions and duplications using cell‐based noninvasive prenatal testing

Abstract: Objective To gather additional data on the ability to detect subchromosomal abnormalities of various sizes in single fetal cells isolated from maternal blood, using low‐coverage shotgun next‐generation sequencing for cell‐based noninvasive prenatal testing (NIPT). Method Fetal trophoblasts were recovered from approximately 30 mL of maternal blood using maternal white blood cell depletion, density‐based cell separation, immunofluorescence staining, and high‐resolution sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 23 publications
2
79
0
Order By: Relevance
“…[ 30,31 ] Cell‐based testing has several advantages over cffDNA‐based test, in that fetal cells provide pure fetal DNA of high integrity. [ 32 ] A total of 11 pregnancies whose fetuses may carry thalassemia mutations were investigated: five were at risk for – SEA / thalassemia and six were at risk for β‐thalassemia. Thalassemia‐related mutations could be reliably detected by analyzing these rare fetal cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30,31 ] Cell‐based testing has several advantages over cffDNA‐based test, in that fetal cells provide pure fetal DNA of high integrity. [ 32 ] A total of 11 pregnancies whose fetuses may carry thalassemia mutations were investigated: five were at risk for – SEA / thalassemia and six were at risk for β‐thalassemia. Thalassemia‐related mutations could be reliably detected by analyzing these rare fetal cells.…”
Section: Discussionmentioning
confidence: 99%
“…More people are becoming aware that there are fetal chromosomal abnormalities other than trisomy 21, trisomy 18, and trisomy 13 [5,6] that lead to neonatal birth defects, and the prevalence rate of these other chromosomal abnormalities is rising [7]. Compared to traditional serological screening, noninvasive prenatal testing (NIPT) has been welcomed by pregnant women and clinicians for fetal chromosomal aneuploidy screening due to its high detection rate, low false positive rate, and noninvasiveness [8,9]. However, a large portion of the literature has focused on the study of common chromosomal aneuploidy and has rarely reported on other chromosomal abnormalities [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the cell-based approach has limitations, it has been shown that individual fetal cells can be isolated from maternal circulation and that their pure fetal DNA can be used for the detection of copy number abnormalities of at least 1 Mb by low-coverage NGS. Analysis of the fetal genome at a higher resolution would allow increased accuracy and improved positive and negative predictive values compared with cfDNA-based NIPT in the detection of microdeletion syndromes 48 .…”
Section: Fetal Cell-based Approachmentioning
confidence: 99%